Optimum utilization of megavoltage teletherapy machine in developing countries - Phalguni Gupta; Ranen Kanti Aich; Asit Ranjan Deb; Poulami Gupta (Al Ameen Medical College, 2015)
Objectives: Radiotherapy is an integral part of Cancer management. The unavailability of adequate number of teletherapy machines in developing countries like India has compounded upon the increasing incidence of Cancer, leading to a huge deficit between demand and supply of Radiotherapy facilities. In this scenario, innovations and management techniques are essential to try to make up this deficit and to reduce waiting period. Methods: In 2001, one Telecobalt unit was installed, after dismantling old Telecaesium unit in our Tertiary Care Center at Kolkata. Certain qualitative changes also accompanied the new machine .With these qualitative changes, number of new patients registered and number of radiation exposure was increased. In December 2002, certain decisions were taken to decrease the delay, since implementation our decisions from April 2003. Results: Over twelve years since 2002, 270.25 % increase of new cancer patients (1449 in 2002 and 5365 in 2013) and 290.25 % increase of number of radiotherapy exposures (16790 in 2002 and 65524 in 2013) has been observed in 2013. With change of daily working period and the working pattern, waiting period could be restricted to 30 days in 2013. Conclusions: Certain innovations have been introduced incorporating change of working period and pattern of work for maximum use of Telecobalt machine and have been in effect for the preceding eleven years, which have been proved extremely effective at our centre. They have been presented in this article with a view to disseminate our experience to other Radiotherapy centers facing similar problems to bring down the waiting period.